The Concept of Nozj - Mahdi Alizadeh-Vaghasloo; Mohammad-Ali Zareian; Sayed-Mohamm (Tehran University of Medical Sciences, 2016)
Nozj is a unique heterogeneous complex phenomenon discussed extensively by Traditional Persian Medicine (TPM) scholars, as a rheological change in matter for better consumption or excretion. Nozj is closely related to the many stages of digestion and affects many aspects of health and disease. Nozj status in different parts of body may be assessed and monitored using many signs and symptoms regularly not considered fairly important to other schools of treatment especially the mainstream medicine. Uncompleted process of Nozj leads to accumulation of different substances in different parts of the body. This process, generally be named as the "Bad-anbaasht" syndrome, predisposes a wide variety of famous known medical conditions.